Rubber tapping technical improvement and application in China - Xiaodi Wei; Hanrong Cai; Jialian Wu; Jixian Chen; Xianzhou Xiao (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.265-278.)
Rubber tapping technique reform and application in China began in 1971. This project was included in the development projects of the State Economic Committee, the key projects of the Agricultural Ministry, the 948 projects of the country and etc in different times. It was undertaken by the Chinese Academy of Tropical Agricultural Sciences together with the state farms bureaus of Hainan, Guangdong and Yunnan. The project includes reform and application of tapping techniques for rubber trees from the seedling trees and low-yielding grafted trees to high-yielding grafted trees, from middle and old aged tapping trees to young tapping trees, from relatively stimulation-tolerant clones to moderately stimulation-tolerant clones. Research results showed that rubber tapping with ethrel stimulation had significant effects on increasing rubber yield and tapping labor productivity, saving barks and etc. The physiological condition of the rubber trees was normal without obvious side-effects such as tapping panel dryness. The product quality conforms to the national standard. Great success has been achieved in large-scale extension and application of the reformed tapping system in the country. By the year of 2003, the reformed tapping techniques had been extended to 288 627 hectares in state farms of Hainan, Yunnan and Guangdon provinces in China which accounts for 98.0;of the total rubber plantations of the state farms, increasing 93.47 tons of dry rubber production (i.e. RMB 7.6 billion yuan of production value) accumulatively in 30 years, increasing income and saving expense of RMB 9.238 billion yuan. 116 000 tapping workers are saved only in one year of 2003, economic benefit being very significant.
Keywords: Ethrel stimulation; Extension and application; Rubber tree; Tapping system